2016
DOI: 10.1037/rel0000030
|View full text |Cite
|
Sign up to set email alerts
|

Perceived and actual change in religion/spirituality in cancer survivors: Longitudinal relationships with distress and perceived growth.

Abstract: This observational cohort study examined the relationships between actual and perceived R/S change at 12 months post cancer diagnosis with depression, anxiety, and perceived growth 6 months later. Older adult military veteran cancer survivors (n = 111) completed self-report surveys at 6, 12, and 18 months post cancer diagnosis. Perceived R/S change was assessed at 12 months postdiagnosis with “Have your religious or spiritual beliefs changed as a result of your cancer” (more R/S, less R/S, other). Actual R/S c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…As with research on anxiety disorders, prospective studies examining the effects of religiosity on PTSD report mixed findings, ranging from no effect on symptoms to either worsening or improving. An observational cohort study following 111 older male US military veterans with cancer over 6 months found that increases in religiosity predicted an increase in PTSD symptoms (Trevino 2016). In contrast, a study of 532 US veterans involved in a 60-to 90-day residential treatment programme for combat-related PTSD found that religion/spirituality assessed on admission (baseline) predicted significantly fewer PTSD symptoms at discharge, independent of baseline PTSD severity (Currier 2015).…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…As with research on anxiety disorders, prospective studies examining the effects of religiosity on PTSD report mixed findings, ranging from no effect on symptoms to either worsening or improving. An observational cohort study following 111 older male US military veterans with cancer over 6 months found that increases in religiosity predicted an increase in PTSD symptoms (Trevino 2016). In contrast, a study of 532 US veterans involved in a 60-to 90-day residential treatment programme for combat-related PTSD found that religion/spirituality assessed on admission (baseline) predicted significantly fewer PTSD symptoms at discharge, independent of baseline PTSD severity (Currier 2015).…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…Further, PTGI scores were positively associated with coping efforts and increases in distress. A number of similar studies that have examined changes in actual PTG over time have consistently found that PTGI scores are unrelated changes in actual PTG (Boerner, Joseph, and Murphy, 2017; Kunz, Joseph, Geyh, and Peter, 2018; Ransom, Sheldon, and Jacobsen, 2008; Trevino, Naik, and Moye, 2016; Yanez, Stanton, Hoyt, Tennen, and Lechner, 2011, [20,21,22,23,24]; although, for an important exception, see Iimura and Taku, 2018, [25]). Hence, it appears the PTGI does not assess actual PTG, but rather perceived PTG.…”
Section: Introductionmentioning
confidence: 99%
“…From an evolutionary standpoint, the experience of spirituality and religiousness can be seen as the result of the same advantageous neuronal development responsible for the human tendency to socialize and create communities ( Kirkpatrick, 2005 ). While spirituality has been described most prominently as “the search for significance in ways related to the sacred” ( Pargament, 1999 , p. 4) and therefore as a very personal and affective construct, religiousness is largely defined by specific rituals, ideologies, and institutions ( Pargament, 1999 ).…”
Section: Introductionmentioning
confidence: 99%